1991
DOI: 10.1016/0248-4900(91)90006-9
|View full text |Cite
|
Sign up to set email alerts
|

Human keratinocyte membrane lectins: characterization and modulation of their expression by cytokines

Abstract: In an attempt to identify cell surface molecules involved in recognition phenomena between cells such as keratinocytes and melanocytes and putatively target biological responses modifiers to keratinocytes, we undertook the detection of cell surface sugar specific receptors: membrane lectins. Keratinocyte membrane lectins were found to bind synthetic glycoproteins (neoglycoproteins) carrying either alpha-L-fucosyl or alpha-L-rhamnosyl residues. Fluorescence microscopy observations indicate that cultured keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…If separate from the carbohydrate-binding site, the question on interplay between the two sites will have to be resolved. Looking beyond galectins, experiments with neoglycoproteins document the presence of sugar receptors on keratinocytes, cells of the SCL-1 squamous carcinoma cell line and sections of squamous cell carcinomas with specificities to galactose-6-phosphate, a-L-rhamnose or a-L-fucose, broadening the scope of analysis of lectins in this cell system (Gabius et al 1990;Cerdan et al 1991;Condaminet et al 1997;Minwalla et al 2001;Szolnoky et al 2001). Their biochemical characterization will add to the panel of markers, because activities were found to be UV-B inducible, regulatable by cytokines or partaking in melanosome transfer.…”
Section: Discussionmentioning
confidence: 98%
“…If separate from the carbohydrate-binding site, the question on interplay between the two sites will have to be resolved. Looking beyond galectins, experiments with neoglycoproteins document the presence of sugar receptors on keratinocytes, cells of the SCL-1 squamous carcinoma cell line and sections of squamous cell carcinomas with specificities to galactose-6-phosphate, a-L-rhamnose or a-L-fucose, broadening the scope of analysis of lectins in this cell system (Gabius et al 1990;Cerdan et al 1991;Condaminet et al 1997;Minwalla et al 2001;Szolnoky et al 2001). Their biochemical characterization will add to the panel of markers, because activities were found to be UV-B inducible, regulatable by cytokines or partaking in melanosome transfer.…”
Section: Discussionmentioning
confidence: 98%
“…Rhamnose, commonly found as a glycoconjugate in plants and enteric bacteria, is readily available to mammals from dietary and environmental sources. The ubiquitous presence of this sugar may also explain detection of rhamnose-selective lectins in mammalian cells (21). While identification of L-rhamnose does not rule out the possibility that HIF is an endogenous substance, it also does not distinguish HIF from ouabain.…”
Section: Methodsmentioning
confidence: 99%
“…These cells constitute a major barrier between the internal organism and the external environment and represent 95% of the total epidermal cells. Studies on human keratinocytes and on laboratory rodents have shown that many exogenous and endogenous factors can lead to cutaneous epidermal cell activation (Caughman et al, 1990;Cerdan et al, 1991). Skin exposure to ultraviolet radiation, viral infections, irritants and allergens can induce keratinocyte activation (Chen et al, 1985;Cerdan et al, 1991;Palacio et al, 1997a).…”
Section: Introductionmentioning
confidence: 97%
“…TNF-α can maintain keratinocytes in an activated state (Freedberg et al, 2001). After activation, keratinocytes also express surface molecules such as the intercellular adhesion molecule ICAM-1/CD54, a ligand of the leukocyte function-associated antigen LFA-1 (Caughman et al, 1990;Cerdan et al, 1991). In addition to their frequent autocrine effects, many substances released by the activated keratinocytes act in a paracrine manner on different cell types (T lymphocytes, granulocytes, dendritic cells, Langerhans cells, endothelial cells, fibroblasts and melanocytes) contributing to cellular activation, differentiation and chemotaxis and to induction of adhesion molecule expression (Chen et al, 1985;Caughman et al, 1990;Kock et al, 1990;Kimber and Cumberbatch, 1992;Gueniche et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation